Al-Ghazali, Averros͡ and the interpretation of the Qur'an : common sense and philosophy in Islam - 484493 Wohlman, Avital; Burrell, David B. (London ; New York, NY : Routledge, 2010)
Includes bibliographical references (p. [109]-126) and index